2007
DOI: 10.1017/s1355617707071111
|View full text |Cite
|
Sign up to set email alerts
|

Intensive language training in the rehabilitation of chronic aphasia: Efficient training by laypersons

Abstract: Intense language training has been found to be more efficient in the rehabilitation of chronic aphasia than treatment spread across time. Intense treatment, however, challenges personnel and financial resources of the health care system. The present study examined, whether laypersons can be trained to apply standardized language training for chronic aphasia with effects comparable to training by experts. Twenty individuals with chronic aphasia participated in the training, Constraint-Induced Aphasia Therapy (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 29 publications
1
41
0
Order By: Relevance
“…CIAT is a form of intensive language-action therapy which uses massed, high-frequency rehabilitative training that encourages language use in communicative interaction contexts (Pulvermüller and Berthier 2008;Berthier and Pulvermüller 2011). A growing body of evidence shows that treatment with CIAT is superior to conventional SLT (Pulvermüller et al 2001) and also that CIAT can readily be administered by appropriately trained lay individuals (Meinzer et al 2007). Gains in language performance after CIAT translate to daily functional communication, are maintained over time (Pulvermüller et al 2001;Meinzer et al 2005;Berthier et al 2009) and are associated to plastic reorganization (displacement of a primary language area) of perilesional areas of the left hemisphere with additional recruitment of the intact right hemisphere (Pulvermüller et al 2005;Breier et al 2007;Meinzer et al 2008).…”
Section: Speech and Language Therapymentioning
confidence: 99%
“…CIAT is a form of intensive language-action therapy which uses massed, high-frequency rehabilitative training that encourages language use in communicative interaction contexts (Pulvermüller and Berthier 2008;Berthier and Pulvermüller 2011). A growing body of evidence shows that treatment with CIAT is superior to conventional SLT (Pulvermüller et al 2001) and also that CIAT can readily be administered by appropriately trained lay individuals (Meinzer et al 2007). Gains in language performance after CIAT translate to daily functional communication, are maintained over time (Pulvermüller et al 2001;Meinzer et al 2005;Berthier et al 2009) and are associated to plastic reorganization (displacement of a primary language area) of perilesional areas of the left hemisphere with additional recruitment of the intact right hemisphere (Pulvermüller et al 2005;Breier et al 2007;Meinzer et al 2008).…”
Section: Speech and Language Therapymentioning
confidence: 99%
“…The picture cards contain objects of high as well as low frequent words, black-and-white line drawings as well as colored pictures, pictures of objects as well as action cards, and pictures with minimal pairs (e.g., sock and rock); see Participants Treatments and the Appendix for more details. The intervention procedure was based on Maher et al (2006), Meinzer et al (2005Meinzer et al ( , 2007, and Pulvermüller et al (2001). In this study, patients were allowed to produce gestures in order to facilitate verbal output, but their gestures were hidden from the other participants by a 40-cm high screen between the patient and the other participants.…”
Section: Treatment Programsmentioning
confidence: 99%
“…During the first 2 days of the training, the students remained under the supervision of six experienced and professionally trained speech and language therapists. Students were trained according to the training protocol of laypeople designed by Meinzer et al (2007). The speech and language therapists had been given detailed instructions by means of a 2-hr presentation in which the study was presented.…”
Section: Therapist Trainingmentioning
confidence: 99%
“…Nevertheless, even at reduced intensity, the time (and therefore cost) commitment for speech pathologists remains not inconsiderable. Hence, in the context of funding constraints on speech pathology services, it is of relevance that Meinzer, Streiftau and Rockstroh (2007) found that CIAT administered by trained laypeople produced comparable results to CIAT administered by speech pathologists. With this in mind, we extended our previous study (Osborne & Nickels, 2012;in preparation) to investigate whether less intense CIAT could also be effectively delivered by trained volunteers.…”
Section: Introductionmentioning
confidence: 98%